HAM DALAM PERSPEKTIF ILMU-ILMU SYARIAH - Adil, Muhammad (Nurani, 2013)
Abstract: Transformation of the concept and the idea of human rights values to students early on of course be necessary to do, given the new generations is what will be the successor to the perpetrators of the world. It is expected that all students have the same attention to human values.ملخص: التحول من مفهوم وفكرة قيم حقوق الإنسان للطلاب في وقت مبكر بطبيعة الحال يكون من الضروري القيام به، نظرا للأجيال الجديدة هو ما سوف يكون خلفا لمرتكبي العالم. ومن المتوقع أن جميع الطلاب لديهم نفس القدر من الاهتمام إلى القيم الإنسانية.Kata kunci: hak azasi manusia, ilmu syari'ah.